Performance evaluation of a novel intelligent distributed mounting system for marine mechanical equipment. (29th November 2019) - Qiu, Yuanran; Xu, Wei; Li, Zhengmin
Machinery mounting system is one of the most significant vibration and noise attenuation technology for marine mechanical equipment. A novel intelligent mounting system having distributed intermediate mass light in weight, intelligent in function and small in installation space is presented. The performance of the novel distributed mounting system is analysed using a simplified but efficient theoretical model. The influences of system designing parameters including weight of intermediate mass, stiffness of isolators and mechanical impedance of foundation on vibration isolation efficiency are analysed. A scale experimental prototype was established to verify the accuracy of theoretical analysis. Conclusions of theoretical and experimental analysis reveal that stiffness of isolators should be chosen as small as possible under the premise of stability of system. The intermediate mass should be chosen within a reasonable range based on the index requested on isolation efficiency because substantial increase on intermediate mass will not lead to substantial increase on vibration isolation efficiency which is different from conventional methods to obtain considerable isolation efficiency. And intelligent safety mechanism designed to ensure the ultimate operation safety of equipment was introduced. The novel intelligent mounting system is qualified with the need of practical projects on vibration isolation efficiency and reliability standard, providing a new way for vibration engineer to choose when making mounting plan for marine machinery equipment.